Studi Potensi Gulma Sebagai Tanaman Obat di Kabupaten Jayawijaya - Anti Uni Mahanani (Agrotek, 2015)
The purpose of this research is to identify the potency of gulma plant in jayawijaya region to become medicinal plants. Purposive Sampling method was being used in the data collection. The result of the inventaritation research found that there are 18 weeds utilized as medicine plants in jayawijaya region, namely: : Babandotan (Ageratum conyzoides), Rumput Gajah (Pannisetum purpureum), Putri Malu (Mimosa pudica), Kukuyaan (Corenia violacea), Ciplukan (Physalis angulata L.), Kecimbling Hijau dan Merah (Stachytarpheta mutabilis Vahl), Rumput Teki (Cyperus rotundus), Rumput 9 Dewa, Alang-Alang (Imperata cylindrica), Tapak Kuda/Gagan (Cantella asiatica L.), Patikan Emas (Euphorbia hirta L.), Biji Kacang, Boborongan (hyptis brevipes Poit), Bayam Berduri (Amaranthus spinosus L.), Urang-Aring (Eclipta prostrata L.), Tembelekan (Lantana camara L.), Tunjuk Langit, and Rumput Mutiara (Hedyotis corymbosa (L).